A full-Newton step feasible interior-point algorithm for P*(k)-linear complementarity problems - Wang, G.; Yu, Changjun; Teo, Kok Lay (Springer, 2013)
In this paper, a full-Newton step feasible interior-point algorithm is proposed for solving P*(κ) -linear complementarity problems. We prove that the full-Newton step to the central path is local quadratically convergent and the proposed algorithm has polynomial iteration complexity, namely, O ((1+4κ) √nlogn/ε), which matches the currently best known iteration bound for P*(κ)-linear complementarity problems. Some preliminary numerical results are provided to demonstrate the computational performance of the proposed algorithm.